Aadhunik Bodh Ke Upanyaas Aur Shivani: Exploring the Contemporary Enlightenment in Hindi Novels and Shivani's Works (Journal of Advances and Scholarly Researches in Allied Education, 2012)
dqN fo}kuksa us Lokra=;ksRrj miU;klksa dks ^vk/kqfudrk&cks/k^ ds :iesa Lohdkj fd;k gSA lkBksRrjh miU;kl ^vk/kqfudrkoknh^ fopkj/kkjk lsfo’ks"k :i ls izHkkfor gSaA